Determinan Servant Leadership terhadap Employee Loyalty Melalui Job Satisfaction sebagai Variabel Intervening - Ida Ayu Wiliastiti; I Gusti Putu Agung Widya Goca; Cokorda Istri Agung Vera Nindia Putri (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study examines the influence of servant leadership style on employee loyalty, both directly and indirectly through job satisfaction, at PT Graha Sarana Duta (Telkom Property) Bali Area. Research Methodology: This is a quantitative research using a survey-based non-experimental approach. Data were collected from 76 outsourcing employees selected through simple random sampling. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS 3.0. The study is underpinned by Equity Theory, which explains that perceptions of fairness influence both job satisfaction and employee loyalty, especially in relation to leadership behavior. Results: The results indicate that servant leadership positively affects job satisfaction and employee loyalty, with job satisfaction also acting as a partial mediator in this relationship. Conclusion: Servant leadership, marked by love, humility, and support, enhances job satisfaction and ultimately boosts employee loyalty, highlighting the importance of empathetic and service-oriented leadership. Limitations: This study focuses on outsourcing employees in a single company with a cross-sectional design, limiting its ability to capture long-term effects. Future research should consider additional variables like work environment or company policies for broader insights. Contribution: This study contributes by validating Equity Theory in the context of employee loyalty and job satisfaction in Indonesia’s property sector, while offering practical insights for enhancing retention through servant leadership.